A NARRATIVE REVIEW OF SKIN SYMPTOMS IN PSYCHIATRY AND PSYCHOLOGICAL CO-MORBIDITY IN DERMATOLOGY. - Jahan, Firdous; Zafar, Md. Shahanawaz (Student's Journal of Health Research Africa, 2024)
Objective This narrative review aims to elucidate the intricate relationship between dermatological and psychological conditions, emphasizing the importance of a collaborative approach between dermatologists and psychiatrists. By exploring the physiological and psychological interactions contributing to various skin disorders and their mental health implications, the review seeks to provide a comprehensive understanding that can inform future clinical practices and research. Summary The review underscores the dual origin of the skin and nervous system from the ectoderm, highlighting their interconnectedness. Chronic stress and psychological conditions such as depression and anxiety are shown to exacerbate skin conditions like alopecia, eczema, and psoriasis. Conversely, visible skin conditions can lead to significant psychological distress, contributing to mental health disorders such as depression and anxiety. The review categorizes psychodermatological conditions into three main types: psychophysiological disorders, which are skin conditions triggered by underlying psychological issues; primary psychiatric conditions, where skin disorders result directly from psychiatric disorders; and secondary psychiatric conditions, where psychological issues arise from primary skin conditions. Application for Future Research The narrative review proposes several avenues for future research. Comprehensive clinical trials are needed to explore effective treatments for psychodermatological conditions, providing evidence-based strategies for managing these disorders. Incorporating psychodermatology into medical education can better equip future dermatologists to handle these complex cases, fostering a more integrated approach to patient care. Developing models for collaborative care involving both dermatologists and psychiatrists can enhance treatment efficacy and improve patient outcomes. Additionally, longitudinal studies focusing on the long-term outcomes of patients receiving combined dermatological and psychological treatment can provide deeper insights into the effectiveness of this approach.